Predictors of Anastomotic Leak After Esophagectomy for Cancer: Not All Leaks Increase Mortality. Issue 6 (June 2021) - Krasnoff, Chloe C.; Grigorian, Areg; Smith, Brian R.; Jutric, Zeljka; Nguyen, Ninh T.; Daly, Shaun; Lekawa, Michael E.; Nahmias, Jeffry
Background: The impact of preoperative chemotherapy/radiation on esophageal anastomotic leaks (ALs) and the correlation between AL severity and mortality risk have not been fully elucidated. We hypothesized that lower severity ALs have a similar risk of mortality compared to those without ALs, and preoperative chemotherapy/radiation increases AL risk. Methods: The 2016-2017 American College of Surgeons National Surgical Quality Improvement Program's procedure-targeted esophagectomy database was queried for patients undergoing any esophagectomy for cancer. A multivariable logistic regression analysis was performed for risk of ALs. Results: From 2042 patients, 280 (13.7%) had ALs. AL patients requiring intervention had increased mortality risk including those requiring reoperation, interventional procedure, and medical therapy ( P < .05). AL patients requiring no intervention had similar mortality risk compared to patients without ALs ( P > .05). Preoperative chemotherapy/radiation was not predictive of ALs ( P > .05). Conclusion: Preoperative chemotherapy/radiation does not contribute to risk for ALs after esophagectomy. There is a stepwise increased risk of 30-day mortality for ALs requiring increased invasiveness of treatment.